Factors associated with delayed use of antenatal care in sub-Saharan Africa. - , NGOY SHABANI Claude; PASCAL KIBONGE; NKAMBA KANKOLONGO Hattie; SHABANI MACHOZI; ASSANI WAKENGE Bonny; MAOLE NGOY Juresse; MASUMBUKO TEMBEA LEA; Gedeon Kalonda Bwanahali (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Antenatal care (ANC) is essential for early detection of pregnancy complications. The WHO recommends an initial visit before 12 weeks of gestation. However, in sub-Saharan Africa, many women initiate care late, often after the fourth month of pregnancy, compromising the expected benefits. A narrative review was conducted using a literature search in PubMed, Google Scholar, and Hinari, including articles published between 2002 and 2022, in English and French. Frequency of late ANC use: 81.6% of women who initiated ANC late were aged 20 to 34 years, 61.75% had a parity of 2 to 4, 97.87% were married, and 60.4% had a secondary education. Coverage: 56.47% of women who had ≥ 4 antenatal consultations started them late, compared to only 14.42% who had ≥ 4 early consultations. ; Factors associated with delay: Residence in a rural area (OR = 2.156); lack of education (OR = 3.24); age ≥ 25 years (OR = 1.62); unplanned pregnancy (OR = 2.16); monthly income ≤ 1000 ETB (≈ 50 USD) (OR = 1.77); lack of knowledge of the start date of ANC (OR = 1.8); multigravity (OR = 2.575). Delay in the first ANC is common and multifactorial. Targeted interventions are needed, particularly in the areas of education, family planning, community awareness and improvement of the quality of services. The most vulnerable women (poorly educated, elderly, multiparous) must be given special attention in public health policies to reduce maternal mortality in sub-Saharan Africa